The Influence of Temperature on the Removal of Biodegradable Organic Carbon - Welté, B.; Montiel, A. (Revue des sciences de l'eau / Journal of Water Science, 1996)
A study of the removal of dissolved organic carbon (DOC) and biodegradable dissolved organic carbon (BDOC) has been performed in a water treatment plant where several biological steps are involved. The influence of the temperature of the raw water has been studied. The behavior of slow sand filtration (SSF) differs from that of granular activated carbon (GAC) filtration: in the case of slow sand filtration, optimum efficiency is obtained at a temperature above or equal to 15°C, whereas optimum efficiency for GAC is obtained starting from a temperature of 10°C. Slow sand filtration seems to be more efficient in BDOC removal where high temperatures are present. For low temperatures, efficiency of the two methods is comparable. For medium temperatures (10°C), GAC seems to be more efficient.